Quantification of mixing processes in mine water with low- or high‑sulfur minerals by a stable isotope mass balance - Xie, Huanhuan; Sun, Jing; Strosnider, William H.J.; Zhang, Ruixue; Li, Xuexian; Wu, Pan (Journal of contaminant hydrology, 2025)
Trace elements from metal sulfide-bearing strata present a pressing global environmental problem. The geochemistry, treatment, and reuse of trace elements in mine water are closely related to the occurrence and abundance of sulfur (S) in low sulfurous (LS) and high sulfurous (HS) minerals. To identify the relationship between S and trace elements, the hydrogeochemical variability of HS and LS waters with mining activities was investigated. With increased mining disturbance, the HS and LS waters were generally characterized by low pH and high levels of iron (Fe), aluminum (Al), manganese (Mn), copper (Cu), and sulfate (SO42−) exceeding United Nations Food and Agriculture Organization irrigation water standards. Most of HS and LS waters were characterized by high levels of SO42−, Fe, Al, and Mn under acidic conditions, while contents of SO42−, Fe, and Mn in HS water were higher than LS under alkaline conditions. That is probably attributed that the modes of S occurrence are sulfide and sulfate in high sulfurous coal, and volatile and organic matter in low sulfurous coal. Coupling the compositions of stable S and O isotopes and the concentrations of SO42−, Fe, and Ca indicated that HS and LS waters were subject to pyrite oxidation, evaporite dissolution, and rainfall, in accordance with the results of principal component analysis. Based on a stable isotope mixing model, contributions of pyrite oxidation, evaporite dissolution, and rainfall were 87 %, 7 %, and 6 % for HS water, and 84 %, 4 %, and 12 % for LS water. Although there are similar contribution ratios of the three end members to HS and LS waters, the water quality has different responses to them under acid and alkaline conditions. It suggests that both end members and S occurrence modes are of importance to water quality. This is beneficial to make abatement plans for trace element contamination in different conditions. •Trace elements in mine water are closely related to low- or high-sulfur (LS or HS) minerals.•Most of HS and LS waters exhibited high levels of sulfate, and trace elements under acidic conditions.•Contents of these components in HS water were higher than LS under alkaline conditions.•Sulfate sources are pyrite oxidation (86 %), evaporite dissolution (5 %), and rainfall (9 %).